WEBINAR AS AN INNOVATIVE TECHNOLOGY OF ONLINE EDUCATION WITH THE USE OF MODERN MEDIA RESOURCES - Vladislavovna Agaltsova, Darya; Agaltsova, Darya; Rodionova, Nadezhda; Raushana Beisenovna, Sabekia; Saratovich Kagosyan, Ashot; Ostroukhov, Vladimir (Revista Inclusiones, 2020)
Modern information and communication technologies allow creating a powerful e-education environment that is rapidly developing and blurring the boundaries between traditional formal and informal learning. A properly organized use of created learning environments encourages research and teaching staff to seek and find innovative methods of teaching and research activities, motivates them to cognitive activities, and develops students' skills for self-study. The article describes the features of creating and using webinar as an innovative technology of online education with the use of modern media resources (on the example of YouTube). Based on a pedagogical experiment on the introduction of webinar technology into the professional training of future specialists in humanities with the help of YouTube, it has been concluded that this technology will improve the performance and quality of training of future specialists in humanities.